Possible effect of threshing method on grain iron and zinc density estimation in pearl millet: a contribution to biofortification breeding - Mahalingam Govindaraj (Electronic Journal of Plant Breeding, 2017)
In crop biofortification research, threshing part is the primary place of contamination while dealing with grain mineral traits such as iron (Fe) and zinc (Zn) density, thus type of threshing operation is one of the important and effective factors for efficient grain mineral traits determination. This study is aimed at the effects of threshing methods namely power-operated single-head thresher and manual-hand threshing on Fe and Zn density estimation. In this context, 50 pearl millet progenies each from two broad-based populations (AIMP 92901 and ICMR 312) were evaluated in field condition and tested for machine and hand threshing. Grain samples were analyzed for Fe and Zn density using Inductively Coupled Plasma Optical-Emission Spectrometry (ICP-OES) method. The analysis of variance showed the significant difference among population progenies for these micronutrients by recording two-fold variations for Fe (40-91 mg kg-1) and Zn (32-74 mg kg- 1) density. Threshing method had significant effect, however, estimated Fe and Zn values from both the methods were highly comparable, further non-significant t-test and linear correlations-coefficients showed machine-threshed samples results were highly positively significantly correlated with hand-threshed samples values for both micronutrients (r=0.88 to 0.93; p<0.01 for Fe and r= 0.92 to 0.95; p<0.01 for Zn) in two populations. This study indicating the high levels of consistency on ranking of test entries and threshing method has no effect on grain Fe and Zn estimation. Therefore, singlehead thresher will be a reliable and faster method for large-number of breeding materials threshing and its grain micronutrient determination in pearl millet biofortification.